FIRST RECORD OF Polymixia nobilis LOWE, 1838 (ACTINOPTERYGII: POLYMIXIIDAE) IN CEARÁ STATE, BRAZIL - de Paiva, Carolina Cerqueira; de Salles, Rodrigo; de Araújo, Maria Elisabeth (Arquivos de Ciências do Mar, 2009)
The species Polymixia nobilis Lowe, 1838 (Actinopterygii: Polymixiidae) is recorded for the fi rst time in the state of Ceará, Brazil, based on one specimen collected on the Aracati Seamount at a 205 meter depth. Moreover, new meristic and morphologic data are presented.